Impact of the COVID-19 Pandemic on Physicians Working in the Head and Neck Field - Imamura, Rui; Bento, Ricardo F.; Matos, Leandro L.; William, William N., Jr.; Marta, Gustavo N.; Chaves, Aline L. F.; Castro, Gilberto de, Jr.; Kowalski, Luiz P. (International Archives of Otorhinolaryngology, 2021)
Background With the COVID-19 pandemic, the clinical practice of physicians who work in the head and neck field in Brazil dropped dramatically. The sustained impact of the pandemic is not known.Methods An anonymous online survey was distributed to Brazilian otolaryngologists, head and neck surgeons, medical and radiation oncologists, asking about their clinical practice in the third to fourth months of the pandemic.Results The survey was completed by 446 specialists. About 40% reported reduction of more than 75% in outpatient care. A reduction of 90% to 100% in airway endoscopies was reported by 50% of the responders, and the same rate of reduction regarding surgeries (pediatric or nasosinusal) was reported by 80% of them. Family income decreased by 50%, and the psychological burden on physicians was considerable. The availability of personal protective equipment and safety precautions were limited, especially in the public sector.Conclusion COVID-19 is still impacting the head and neck field, and safety concerns may hinder the prompt resumption of elective care.
Keywords: coronavirus; professional practice; occupational groups; health personnel; work